Analisis Penerapan Konsep Syariah Pada OYO Lavender Homestay Pada Masa Pandemi Covid Di Kota Palembang - Deni Fernanda Sohmi; Hilda Hilda; Fakhrina Fakhrina (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Islamic OYO is an OYO that provides lodging, food and drink services, as well as other services for the public, is managed commercially and meets the requirements imposed by the government, industry and islamic. The covid pandemic that started at the end of 2019 until now has had a bad impact on OYO Lavender Homestay because it has experienced a very drastic decrease in the number of visitors. The hotel business is a business engaged in the accommodation sector, one of which is OYO Islamic. The OYO sector is also a companion sector for the tourism sector and is also one that operates in the service sector, especially accommodation, the market segment is guests who come for rest or business purposes. Sharia OYO is a business or business that uses the concept of Islamic by incorporating several rules of Islamic principles in it which are the hallmark of every islamic business unit. The purpose of this study was to find out the Analysis of the Implementation of the Islamic Concept at OYO Lavender Homestay During the Covid Pandemic in Palembang City. This research is included in the type of field research using primary data sources and secondary data. The data obtained is in the form of a narrative. This study uses qualitative data analysis methods or techniques using inductive reasoning methods. Based on the results of the study that the covid pandemic had an impact on the number of visitors at OYO Lavender Homestay. In 2019 the number of visitors to OYO Lavender Homestay was 7,663 people. However, in 2020 there was a very drastic decrease with the number of 3,951 people. This number decreased by 51.5% from the previous year. Even though there has been a decrease in the number of visitors, OYO Lavender Homestay still does not want to accept visitors of the opposite sex and does not accept visitors of the opposite sex who do not have an identity or proof of marriage when they experience a very drastic decrease in the number of visitors.